2021
DOI: 10.1128/aem.00061-21
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Regulated Protein CarP Responds to Multiple Host Signals and Mediates Regulation of Pseudomonas aeruginosa Virulence by Calcium

Abstract: Pseudomonas aeruginosa is an opportunistic pathogen causing life-threatening infections. Previously, we showed that elevated calcium (Ca2+) levels increase the production of virulence factors in P. aeruginosa. In the effort to characterize the Ca2+ regulatory network, we identified a Ca2+–regulated β-propeller protein, CarP, and showed that expression of the encoding gene is controlled by the Ca2+-regulated two-component system CarSR. Here, by using a Galleria melonella model, we showed that CarP plays a role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 112 publications
(206 reference statements)
0
7
0
Order By: Relevance
“…Previous studies have identified Ca 2+ regulation of numerous Pa virulence factors ( 33, 34, 79 ) contributing to increased mortality in in vivo infection models ( 35, 49, 80 ). The EF hand Ca 2+ sensor, EfhP, was shown to control Pa Ca 2+ responses including the induction of pyoverdine ( 25 ) and pyocyanin production ( 49 ) and elevated virulence in lettuce leaf and G. mellonella infection models ( 49, 50 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have identified Ca 2+ regulation of numerous Pa virulence factors ( 33, 34, 79 ) contributing to increased mortality in in vivo infection models ( 35, 49, 80 ). The EF hand Ca 2+ sensor, EfhP, was shown to control Pa Ca 2+ responses including the induction of pyoverdine ( 25 ) and pyocyanin production ( 49 ) and elevated virulence in lettuce leaf and G. mellonella infection models ( 49, 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…To count the bacterial cell number, the samples were 10x diluted and spotted onto LB agar plates, and CFU were calculated. For quantitative RT-PCR (RT-qPCR), total RNA was extracted as described above, and cDNA was synthesized using a Transcriptor first-strand cDNA synthesis kit (Roche) and RT-qPCR was performed using SYBR green master mix (Roche, Indianapolis, IN) and a Light Cycler 480 Instrument II (Roche) as described previously ( 111 ). The sequences of PCR primers used for RT-qPCR are provided in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our earlier studies showed that P. aeruginosa responds to elevated levels of extracellular Ca 2+ through increased production of biofilm, secreted virulence factors such as pyocyanin, pyoverdine, and proteases 16 , enhanced virulence in plant 17 and worm 18 models, and increased resistance to antibiotics 19 . Two major Ca 2+ regulatory pathways have been reported, including the Ca 2+ -induced two-component regulatory system CarSR 20 and the membrane Ca 2+ sensor LadS kinase which activates the Gac/Rsm system, controlling the switch to sessile mode of growth 21 .…”
Section: Introductionmentioning
confidence: 99%